How to kill your family eaudiobook A novel. - Mackie, Bella (Blackstone Publishing, 2022)
Outrageously funny, compulsively readable, and subversive, How to Kill Your Family is a wickedly dark romp about class, family, love—and murder. Coming soon as an eight-episode series on Netflix, executive produced and starring Anya Taylor-Joy. Bella Mackie's debut novel is driven by a captivating first-person narrator who talks of self-care and social media while calmly walking the reader through her increasingly baroque acts of murder. But then, Grace is imprisoned for a murder she didn't commit. When Grace Bernard discovers her absentee millionaire father has rejected her dying mother's pleas for help, she vows revenge and coldly sets out to get her retribution—by killing them all, one by one.